ANALISIS HUBUNGAN ANTARA PREEKLAMPSIA DENGAN BERAT BADAN, PANJANG BADAN DAN LINGKAR KEPALA BAYI BARU LAHIR DI RS BUAH HATI CIPUTAT TAHUN 2018 - Nabillah Virginia Defanty (2020)
Preeclampsia is the cause of 15-20% of deaths of pregnant women throughout the world and the major cause of infant mortality and morbidity worldwide. The frequency of preeclampsia is around 3-10% in Indonesia. Preeclampsia was associated with fetal growth restriction caused by decreased uteroplacental perfusion which will have an impact on the anthropometric results of infants. The purpose of this study was to determine the relationship between preeclampsia with birth weight, birth length, and head circumference of infants at Buah Hati Ciputat Hospital in 2018. The method was observational analytic with a cross-sectional design on 130 mothers with preeclampsia at Buah Hati Ciputat Hospital, taken by random sampling technique. Research data were collected using medical record sheets in the form of anthropometric measurement data of infants. Research data analyzed with the Chi-Square test showed there was a relationship between preeclampsia with birth weight (p = 0.045) and there was no relationship between preeclampsia with birth length (p = 0.544) and head circumference of infants (p = 0.389). The conclusion, there was a significant relationship between preeclampsia with birth weight while preeclampsia did not have a relationship with birth length and head circumference of infants.